'Change the narrative': The Affair, conceptual evolution and television authorship. Issue 1 (1st March 2022) - Abbiss, Will Stanford
This article assesses the narrative developments of the Showtime series The Affair (2014‐19) alongside the production circumstances reported in the media following its conclusion. Through this, it is argued that actor Ruth Wilson's objections to the direction of her character positively impacted the series, freeing it from the restrictions of its concept and resulting in a more culturally relevant conclusion than could otherwise have been achieved. Sarah Treem's position as showrunner, and the accusations levelled at her by the reports around Wilson's departure, are also investigated, asserting the importance of recognizing the other figures that hold responsibility for a multi-season drama's production environment. Wilson's influence on the trajectory of the series is used to argue against auteur theory, the assumptions of which are identified as attributing sole blame for Wilson's objections to Treem. As it remains unusual for the position of drama showrunner to be held by a woman, the potential harm of such auteurist assumptions is made clear by the example of The Affair.